Validation of the 'FeMorph' software in planning cam osteochondroplasty by incorporating labral morphology. Issue 1 (2nd January 2016) - Masjedi, Milad; Mandalia, Rakhee; Aqil, Adeel; Cobb, Justin
Abstract : Impingement resulting from a cam deformity may cause pain, limit the hip joint range of motion (RoM) and lead to osteoarthritis. We have previously developed FeMorph software to quantify and plan corrective surgery and predict hip RoM post surgery. This study aimed to validate the software and evaluate the influence of the acetabular labrum on hip RoM. Computed tomography data from 92 femur-pelvis pairs were analysed in conjunction with the inter/intra-observer reliability. Four cadaveric hips were dissected, and the three-dimensional (3D) shape and size of the acetabular labrum for these hips was obtained using laser scan. The influence of the acetabular labrum in the RoM and subsequent planning for corrective surgery were then evaluated in cadavers for models with and without a labrum, and used as a first step towards validation of FeMorph RoM prediction. FeMorph was successfully used to model cam deformities and plan corrective surgery. Three-dimensional alpha angles were reduced to below 50° after virtual surgery without an excessive reduction in femoral neck cross-sectional area, which could increase fracture risk. A mean increase of 8° ± 2° in permitted internal rotation was observed during impingement testing following removal of the labrum. FeMorph provides a reliable and useful method to model and plan cam deformity correction. This study indicates that the presence of the labrum is responsible for a substantial decrease in permitted internal rotation at the hip joint. This has implications for surgical planning models which often only account for bony impingement.